Dakwah Walisongo dalam Penyebaran Islam di Indonesia - Kurniawan; Yanti, Fitri; Hermanto, Agus; Sukri, Sukri; Andri, Kurniawan (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2024)
The development of Islamic teachings in the archipelago cannot be separated from the role of Walisongo. Walisongo preached and broadcast Islamic teachings in Java in the 14th century. Long before Walisongo’s arrival, they still used a da’wah system with the pattern of inviting communities of various beliefs to follow Islamic teachings and this took place with little response because the community still strongly followed the traditions of their ancestral religious teachings. After Walisongo’s arrival, the da’wah system used implemented several methods that attempted to change old things that were not in accordance with Islam through a cultural approach. With the da’wah methods used by Walisongo, Islam quickly entered and developed in the archipelago. The propagation of Islam in the process of its spread in Java has been etched in history and the success of the Guardians is recognized as having expanded the adherents of the Islamic religion to the majority of Indonesian society, especially Java, both in urban, rural and mountainous areas. This is proven by the construction of mosques as places of worship and as places to teach religion. This research aims to determine the role and methods of da’wah used by Walisongo in the development of Islamic culture in Indonesia. The method used is a qualitative method with a descriptive approach and literature study as a data collection technique.